Dielectric properties of nanosilica/low-density polyethylene composites: The surface chemistry of nanoparticles and deep traps induced by nanoparticles - S. Ju; M. Chen; H. Zhang; Z. Zhang (eXPRESS Polymer Letters)
Four kinds of nanosilica particles with different surface modification were employed to fabricate low-density polyethylene (LDPE) composites using melt mixing and hot molding methods. The surface chemistry of modified nanosilica was analyzed by X-ray photoelectron spectroscopy. All silica nanoparticles were found to suppress the space charge injection and accumulation, increase the volume resistivity, decrease the permittivity and dielectric loss factor at low frequencies, and decrease the dielectric breakdown strength of the LDPE polymers. The modified nanoparticles, in general, showed better dielectric properties than the unmodified ones. It was found that the carrier mobility, calculated from J–V curves using the Mott-Gurney equation, was much lower for the nanocomposites than for the neat LDPE.